Nanobody-targeted photodynamic therapy for the treatment of feline oral carcinoma: a step towards translation to the veterinary clinic - Beltrán Hernández Irati; Grinwis Guillaume C.M.; Di Maggio Alessia; van Bergen en Henegouwen Paul M.P.; Hennink Wim E.; Teske Erik; Hesselink Jan W.; van Nimwegen Sebastiaan A.; Mol Jan A.; Oliveira Sabrina (Nanophotonics, 2021)
Nanobody-targeted photodynamic therapy (NB-PDT) has been developed as a potent and tumor-selective treatment, using nanobodies (NBs) to deliver a photosensitizer (PS) specifically to cancer cells. Upon local light application, reactive oxygen species are formed and consequent cell death occurs. NB-PDT has preclinically shown evident success and we next aim to treat cats with oral squamous cell carcinoma (OSCC), which has very limited therapeutic options and is regarded as a natural model of human head and neck SCC. Immunohistochemistry of feline OSCC tissue confirmed that the epidermal growth factor receptor (EGFR) is a relevant target with expression in cancer cells and not in the surrounding stroma. Three feline OSCC cell lines were employed together with a well-characterized human cancer cell line (HeLa), all with similar EGFR expression, and a low EGFR-expressing human cell line (MCF7), mirroring the EGFR expression level in the surrounding mucosal stroma. NBA was identified as a NB binding human and feline EGFR with comparable high affinity. This NB was developed into NiBh, a NB-PS conjugate with high PS payload able to effectively kill feline OSCC and HeLa cell lines, after illumination. Importantly, the specificity of NB-PDT was confirmed in co-cultures where only the feline OSCC cells were killed while surrounding MCF7 cells were unaffected. Altogether, NiBh can be used for NB-PDT to treat feline OSCC and further advance NB-PDT towards the human clinic.